Green Approach: ‘‘A Forwarding Step for Curing Leishmaniasis—A Neglected Tropical Disease’’ - Sharma, Lakshika; Dhiman, Mamta; Singh, Abhijeet; Sharma, M. M. (Frontiers in Molecular Biosciences, 2021)
The present review focuses on a dreaded vector-mediated leishmaniasis, with the existing therapeutic approaches including a variety of drugs along with their limitations, the treatment with natural compounds, and different types of metal/metal oxide nanoparticles (NPs). As evidenced, various metallic NPs, comprising silver, silver oxide, gold, zinc oxide, titanium, lead oxide, etc., played a curative role to treat leishmaniasis, are also presented. Keeping in view the advance success of vaccines against the prevalent dreaded diseases in the past and the present scenario, efforts are also being made to develop vaccines based on these NP formulations.